A new species of the calcareous sponge genus Leuclathrina (Calcarea: Calcinea: Clathrinida) from the Maldives - Voigt, Oliver; Ruthensteiner, Bernhard; Leiva, Laura; Fradusco, Benedetta; Wörheide, Gert (Zootaxa, 2018)
The diversity and phylogenetic relationships of calcareous sponges are still not completely understood. Recent integrative approaches combined analyses of DNA and morphological observations. Such studies resulted in severe taxonomic revisions within the subclass Calcinea and provided the foundation for a phylogenetically meaningful classification. However, several genera are missing from DNA phylogenies and their relationship to other Calcinea remain uncertain. One of these genera is Leuclathrina (family Leucaltidae). We here describe a new species from the Maldives, Leuclathrina translucida sp. nov., which is only the second species of the genus. Like the type species Leuclathrina asconoides, the new species has a leuconoid aquiferous system and lacks a specialized choanoskeleton. Phylogenetic analyses of the partial 28S ribosomal RNA gene revealed that L. translucida sp. nov. is most closely related to a clade containing the exclusively asconoid genera Ascandra, Levinella and Soleneiscus, and to a clade of the likewise asconoid genus Ernstia. No close relationship exists to other members of the polyphyletic family Leucaltidae, or to any other leuconoid Calcinea. Our results suggest that the leuconoid aquiferous system of Leuclathrina evolved independently from that of other calcineans and that the family assignment of the genus has to be reconsidered. Because the latter requires a more comprehensive family level revision among many genera of Calcinea, we propose to formally retain the genus in Leucaltidae for the time being.